Color Variation from Vehicle on The Road and Its Environment Through Subtle Motion Study Case - Septian Enggar Sukmana; Farah Zakiyah Rahmanti (Journal of Applied Intelligent System, 2018)
Road accident has been serious case in Indonesia, the big number of the cases is not decreasing for six years. Many ways have been done, one of example is exploiting smart camera or CCTV to observe mocement estimation explicitly or implicitly. One problem is when explicit-based technique is applied, the computation process would take more resource. Implicit-based technique like exploitting processing-based frequency domain must be tried to make a better study and produce more knowledge in this study field. Color magnification can helpful information to support better movement estimation. This eulerian-based technique may be the one useful method to help this study. This paper implements eluerian video magnification to get color magnification on road as observed environment. This technique produces unexpected result that unknown black color appears, it still ambiguous because some scene can be described as black color object magnification result and another is shocking camera effect so that the technique is difficult to obtain color magnfication result. PSNR results quite better value because in spite of color magnification result distraction, the scenery of the road is not covered fully. SSIM shows that some mapping in each video data can not results same pattern, it is suspicious that SSIM mapping is affected by this color magnification result.